Unsur-Unsur Filsafat Yunani dan Relevansinya dengan Pendidikan Agama Islam - Faizal Djabidi (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2016)
Education is a process of improving the quality of human beings in terms of knowledge, personality in order to achieve the perfection of life in the world. Islam as a religion rahmatan lil Alamin through the Qur'an explains in detail and clearly about Islamic education that is blessing and perfection in dealing with life in the world and the hereafter through a process of changing behavior and morals in personal life or social life and life in the natural surroundings. The concept of Islamic education as a process of directing human development (ri'ayah) in the Islamic era, reason, behavior, and social and religious life is directed towards the good towards perfection. The birth of Greek philosophy as the beginning of the centralization of science at that time was based on several aspects and factors first Rich in myths (fairy tales), such as the poetry of Homer, Orpheus, the second work of Homerus has a very important position to guide the life of the Greeks. Third Influence of knowledge originating from Babylon in the Nile River Valley. There are several reasons for Greek philosophy affiliated with Islamic education because of Iskandar Agung's policy that did not destroy Persian civilization and culture, but instead, he tried to unify Greek and Persian culture and make Antioch, Bactra became the center of Greek science and philosophy so that it influenced the religious and non-religious sciences.